A Comparative Study of Shigru Kwath and Yavak Kshara in the Management of Mutra Ashmari w.s.r to Urolithiasis - Yadav, Munni; kumari, Sunil; Yadav, Pankaj (International Research Journal of Ayurveda & Yoga, 2022)
he formation/cause of Ashmari, according to Ayurved Srotovaigunya, is due to Dushit Kapha located in Basti in conjunction with Pradushit Vata and Pitta. Dosha vitiation begins in the Mutravaha Sansthan, is catalyzed by the presence of an incipient lesion, and is eventually blamed for the pathophysiology of Mutrashmari. Excruciating pain over Nabhi, Vasti, or at Sevani, Medra during micturition, sudden stoppage of urine flow, blood stained urine, twisting and slitting of urine, aggravation of pain during running, toileting, and other symptoms of Mutrashmari continue in accordance with symptoms of urolithiasis as defined by modern science. Urolithiasis is the third most prevalent urinary tract disease. Urolithiasis causes pain, lost work time, medical bills, hospitalization, and renal failure in the most productive years of life.